Bone marrow infiltrated Lnc-INSR induced suppressive immune microenvironment in pediatric acute lymphoblastic leukemia. Issue 10 (October 2018) - Wang, Yaping; Yang, Xiaoyun; Sun, Xiaoyan; Rong, Liucheng; Kang, Meiyun; Wu, Peng; Ji, Xiaohui; Lin, Rufeng; Huang, Jie; Xue, Yao; Fang, Yongjun
Abstract Immune escape due to immunosuppressive microenvironments, such as those associated with regulatory T (Treg) cells is highly associated with initial occurrence and development of solid tumors or hematologic malignancies. Here, we employed high-throughput transcriptome screening to demonstrate immunosuppression-associated increases in the long noncoding (lnc) RNA lnc-insulin receptor precursor (INSR), which was corrected with INSR expression in CD4+ T cells extracted from the bone marrow of patients with childhood acute T lymphoblastic leukemia. Loss-of-function and gain-of-function assays in vitro and in vivo revealed that membrane-localized and cytoplasm-localized lnc-INSR promoted Treg distribution and decreased the percentage of cytotoxic T lymphocytes, which induced tumor growth. Through direct binding with INSR, lnc-INSR blocked the INSR ubiquitination site, causing abnormal activation of INSR and the phosphatidylinositide 3-kinase/AKT-signaling pathway. These results indicated that lnc-INSR might promote immune suppression by enhancing Treg-cell differentiation and serve as valuable therapeutic targets in the immunosuppressive tumor microenvironment.